A phenomenological perspective of children's writing - Healey, B.; Merga, Margaret (Australian Literacy Educators' Association, 2017)
Classroom teachers would recognise the struggle of engaging all students in producing quality writing assignments. This might be the view from the outside, but the world experienced by the child during the act of writing may be comprised of potentially rich and significant meaning that is waiting to be uncovered. This paper explores writing research from cognitive, affective, and social perspectives as the foundations for the major determinants on children's writing experience and engagement. In light of modern trends in technology and pedagogy, we argue for a shift in perspective that views these determinants as crucial factors constituting and shaping the lived experience of the act of writing. Drawing upon various disciplines, we suggest a new phenomenological orientation that positions writing as an experience of the self, the expression of ideas, and the existential phenomena of the lifeworld, to investigate this rarely addressed field of writing research. We offer an emergent preliminary working framework useful for informing pedagogical approach, and we highlight future phenomenological research needed in this area.